Angka Kegagalan Pengobatan Klorokuin pada Penderita Malaria Falsiparum Ringan di Daerah dengan Beda Endimisitas (Kajian dengan Teknik PCR dan Konvensional):Treatment Failure of Chloroquine for Uncomplicated falciparum Ma - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Malaria remains problematic and increasing in several areas of Indonesia. In Indonesia, only four antimalarial drugs are available. Drug resistance or treatment failure is one of the main obstacles in controlling the disease in some areas. Treatment failures to antimalaria drugs are increasing. Chloroquine is the standard (first-line) antimalarial drug for clinical malaria treatment and the blood schizontocide component of radical treatment. The first case of chloroquine resistant Plasmodium falciparum in-vivo was documented in East Kalimantan in 1973. Chloroquine resitance has now spread to all provinces since first reported in Indonesia in 1992. Data from all previous evaluation in Indonesia of resistance to antimalaria drugs using in-vivo methods have been based on parasitological response only However there is a need to assess the therapeutic efficacy of current national antimalarial drugs based on parasitological and clinical response. The aims of these study is to determine the therapeutic efficacy chloroquine for the treatment of uncomplicated falciparum malaria, and to compare the efficacy of chloroquine in low (hipo-mesoendemic) and high (meso-hyperendemic) endemic area. The study was started at the end of January 2002. To speed up the patients recruitment, the study was done in five health community centers (Banjarmangu-1, Banjarmangu-2, Tanjung Uban, Kijang and Gantung). The health community center was selected according to the following criteria: (1) located in a hypo-mesoendemic and meso-hyperendemic malaria area with antimalarial drug resistance problem, (2) accessible, (3) outpatient clinic run by a physician and paramedical staff, and microscopy available for the examination of blood slides, (4) number of outpatients above 50/day. Using the World Health Organization protocol for assessment of therapeutic efficacy of antimalaria drugs, it was found that treatment failure in both low and high endemic area are more then 25%, the overall treatment failure were 62,79 /o (low endemic) and 68,81% (high endemic) respectively. Confirmation with PCR technique, treatment failure in the low endemic area showed a level of exactly 51,16%. It was concluded that there was an equal of high proportional chloroquine treatment failure for uncomplicated falciparum malaria treatment in both hypo-mesoendemic and mesohyperendemic area.